1990
DOI: 10.1017/s0305000900010898
|View full text |Cite
|
Sign up to set email alerts
|

Does imitation facilitate the acquisition of grammar? Evidence from a study of autistic, Down's syndrome and normal children

Abstract: A B S T R A C TThis paper re-opens the question of whether imitation plays a significant role in the acquisition of grammar. Data for this study came from four samples of naturalistic mother-child speech taken over the course of one year from four autistic, four Down's syndrome and four normal children, covering a range of MLU stages. In general, autistic children used more formulaic language, including imitations, than Down's syndrome children, who in turn used more than the normal children. Comparisons of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 29 publications
2
43
1
3
Order By: Relevance
“…For most of the children with autism, however, the rate of growth was slower than in typically developing children. The researchers also found that children with ASD and Down syndrome acquired grammatical structures in the same order as typically developing children (Tager-Flusberg, et al, 1990;Tager-Flusberg & Calkins, 1990). …”
Section: Speech and Language Impairmentsmentioning
confidence: 89%
“…For most of the children with autism, however, the rate of growth was slower than in typically developing children. The researchers also found that children with ASD and Down syndrome acquired grammatical structures in the same order as typically developing children (Tager-Flusberg, et al, 1990;Tager-Flusberg & Calkins, 1990). …”
Section: Speech and Language Impairmentsmentioning
confidence: 89%
“…A.L. (age 7, Brundson, Coltheart, Nickels, & Joy, 2006;previously reported in Joy & Brundson, 2002) exhibited echolalia (rote repetition of phrases out of context)-again a common feature of speech development in ASD (Tager-Flusberg & Calkins, 1990). Concerns regarding ASD were also raised in the case of K. (age 4, Schmalzl et al, 2008b), although she did not score in the autistic range on the Childhood Autism Rating Scale (Schopler, Reichler, DeVellis, & Daly, 1980).…”
mentioning
confidence: 84%
“…Most research on spontaneous spoken language in children with ASD has been based on unstructured or loosely-structured interactions with a mother, including play (e.g., Hale & Tager-Flusberg, 2005; Swensen, Kelley, Fein, & Naigles, 2007; Tager-Flusberg & Calkins, 1990; Tager-Flusberg et al, 1990). Such research on spontaneous expressive language in children with ASD has revealed significant deficits in domains of structural language ability.…”
Section: Language Sampling For Children With Asdmentioning
confidence: 99%